2015
DOI: 10.2166/wst.2015.368
|View full text |Cite
|
Sign up to set email alerts
|

An event-based hydrologic simulation model for bioretention systems

Abstract: Bioretention systems are designed to treat stormwater and provide attenuated drainage between storms. Bioretention has shown great potential at reducing the volume and improving the quality of stormwater. This study introduces the bioretention hydrologic model (BHM), a one-dimensional model that simulates the hydrologic response of a bioretention system over the duration of a storm event. BHM is based on the RECARGA model, but has been adapted for improved accuracy and integration of pollutant transport models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
0
8
1
Order By: Relevance
“…R 2 varied from 0.80 to 0.95. K med was 26 mm/h, different from the result achieved byRosendo (2013) of 50 mm/h.…”
contrasting
confidence: 78%
See 1 more Smart Citation
“…R 2 varied from 0.80 to 0.95. K med was 26 mm/h, different from the result achieved byRosendo (2013) of 50 mm/h.…”
contrasting
confidence: 78%
“…These thicknesses represent mean values because they changed slowly along the length. Rosendo (2013) and Menezes (2015) detailed the sizing.…”
Section: Studied Areamentioning
confidence: 99%
“…As illustrated in Figure 2, the model is based on the following sequence of processes explained using the case area: mathematical models of retention units are included in most of the major software packages for simulating drainage systems (e.g., [41][42][43]), and more detailed stand-alone models have also been developed (e.g., [44,45]). However, for our purpose, the complexity of these models was unnecessary and unwanted.…”
Section: Hydrological Model Of Rainwater Flow Through Retention Unitsmentioning
confidence: 99%
“…Three articles were published in 2015 that investigated the hydraulic performance of bioretention cells (Barbu et al, 2015;Jennings et al, 2015;Roy-Poirier et al, 2015). Jennings et al (2015) outlined an algorithm to assess the hydraulic performance of rain gardens using local meteorological data, and concluded that the effectiveness of rain gardens in Ohio was dominated by infiltration rate.…”
Section: Design For Optimization Studies Related Tomentioning
confidence: 99%